The Mediating Role of Inclusive Leadership in the Effect of Organisational Loneliness on Job Stress (Third Sector Social Economic Review, 2025)
The aim of this study is to determine the effect of inclusive leadership on the effect of organisational loneliness on job stress. In addition, the role of inclusive leadership in this interaction was also investigated. In this context, a quantitative research was conducted. The data collected with the questionnaire technique were tested with structural equation modelling (SEM) modelling. As a result of the analyses, it was found that emotional deprivation and social friendship, which are components of organisational loneliness, have a positive and significant effect on time stress and job anxiety, which are components of job stress, and inclusive leadership has a positive and significant effect on time stress and job anxiety dimensions of job stress. According to the mediating effect analysis results obtained by bootstrapping method, it was determined that inclusive leadership did not mediate the relationship between emotional deprivation and time stress, on the other hand, inclusive leadership mediated the relationship between social friendship and time stress, emotional deprivation and job anxiety, and social friendship and job anxiety. The results obtained in the study are expected to contribute to the literature in the field and assist decision-makers in the business world.
Keywords: Organizational Loneliness; Job Stress; Inclusive Leadership; Organisational Behaviour